The 22q11.2 Deletion Syndrome: A Gene Dosage Perspective - Antonio Baldini (The Scientific World Journal)
The 22q11.2 deletion/DiGeorge syndrome is a relatively common “genomic” disorder that results from heterozygous deletion of a 3-Mbp segment of chromosome 22. Of the more than 30 genes deleted in this syndrome, TBX1 is the only one that has been found to be mutated in some patients with a phenotype that is very similar to that of patients with the full deletion, suggesting that TBX1 haploinsufficiency is a major contributor to the syndromes phenotype. Multi- and single-gene mouse models have provided a considerable amount of information about the consequences of decreased and increased dosage of the genomic region (and in particular of the Tbx1 gene) on mouse embryonic development. Modified alleles of Tbx1, as well as conditional ablation strategies have been utilized to map in vivo the tissues and developmental stages most sensitive to gene dosage. These experiments have revealed substantially different sensitivity to gene dosage in different tissues and at different times, underlying the importance of the developmental context within which gene dosage reduction occurs.